Eyelid Margin and Meibomian Gland Characteristics and Symptoms in Lens Wearers. Issue 8 (August 2016) - Cox, Stephanie M.; Berntsen, David A.; Chatterjee, Neil; Hickson-Curran, Sheila B.; Jones, Lyndon W.; Moezzi, Amir M.; Morgan, Philip B.; Nichols, Jason J.
ABSTRACT: Purpose: To describe the lid margin characteristics of contact lens wearers and relate them to comfort during lens wear. Methods: Three study sites enrolled habitual contact lens wearers. Subjects completed the Comfort domain of the Contact Lens User Experience (CLUE) questionnaire, and each eye was graded for the presence of mucocutaneous junction (MCJ) displacement, lid margin irregularity, and lid margin vascularity. Examiners counted the number of meibomian gland (MG) orifices in the central centimeter of the lower eyelid and the number of those that showed pouting/plugging and vascular invasion. MG expressibility was graded according to the Shimazaki schema. Subjects were grouped based on presence/absence of each characteristic, total number of orifices (≥5 vs. <5), and expressibility (grade 0 vs. >0). Descriptive statistics are reported. A linear model was used to assess the fixed effect of each characteristic on combined CLUE score and each CLUE statement, if the effect on combined CLUE score showed p < 0.10. Results: The study included 203 subjects (67.5% female) with mean age (±SD) of 30.3 ± 9.6 years. The most commonly observed characteristics were orifice pouting/plugging, compromised MG expressibility, and lid margin vascularity (35.0, 30.3, and 20.4%, respectively). MCJ displacement and MG expressibility had an effect on the combined CLUE score such that individual CLUE statements were analyzed (p = 0.01 and p = 0.06, respectively). MCJ displacement had an effect on comfort upon insertion (p = 0.01), comfort after 5 minutes (p = 0.03), end-of-day comfort (p = 0.01), and ability to maintain ocular moisture (p = 0.030). MG expressibility had a significant effect on general comfort (p = 0.01), comfort throughout the day (p = 0.02), and the ability to maintain ocular moisture (p = 0.02). Conclusions: MCJ displacement and MG expressibility have an effect on contact lens comfort.